Tailoring of optical properties of fluorescein using green synthesized gold nanoparticles1. Issue 24 (28th June 2015) - John, Jisha; Thomas, Lincy; George, Nibu A.; Kurian, Achamma; George, Sajan D.
<x xml:space="preserve">Abstract</x> The anisotropy in plasmonic field makes star shaped particles as an optical ruler that can probe larger distances as compared to spherical gold nanoparticles, for which dipoles are parallel to the surface act as more efficient quencher for fluorescein dye.